Changes in intraocular pressure after intraocular eye surgery—the influence of measuring technique - Hrvoje Kovacic; Roger C.W. Wolfs; Emine Kılıç; Wishal D. Ramdas (International Journal of Ophthalmology, 2019)
AIM: To investigate the changes in intraocular pressure (IOP) before and after intraocular surgery measured with Goldmann applanation tonometry (GAT) and pascal dynamic contour tonometry (PDCT), and assessed their agreement. METHODS: Patients who underwent trans pars plana vitrectomy (TPPV) with or without cataract extraction (CE) were included. The IOP was measured in both eyes with GAT and PDCT pre- and postoperatively, where the non-operated eyes functioned as control. RESULTS: Preoperatively, mean IOP measurements were 16.3±6.0 mm Hg for GAT and 12.0±2.8 mm Hg for PDCT for the operated eyes. Postoperatively, the mean IOP dropped to 14.3±5.6 mm Hg for GAT (P=0.011) and rose up to 12.7±2.6 mm Hg for PDCT (P=0.257). Bland-Altman analysis showed a poor agreement between GAT and PDCT with a mean difference of 2.9 mm Hg preoperatively and 95% limits of agreement ranging from -3.2 to 9.0 mm Hg. Postoperatively, the mean difference was 1.2 mm Hg with 95% limits of agreement ranging from -8.3 to 10.7 mm Hg. There were no significant differences between the TPPV and TPPV+CE group, except when measured with PDCT postoperatively (P=0.012). CONCLUSION: The IOP is reduced after surgery when measured with GAT and remained stable when measured with PDCT. However, the agreement between GAT and PDCT is poor. Although PDCT may be a more accurate predictor of the true IOP, it seems less suitable for daily use in the clinical practice.